GROWTH REQUIREMENTS OF A HALOPHILIC BLUE-GREEN ALGA, PHORMIDIUM TENUE (MENEGH). - Pillai, V Krishna (Indian Journal of Fisheries, 2016)
IN order to account for the neghgible growth of algas observed in the salinelagoons at Mandapam a complete knowledge of the normal nutritional andgeneral physiological factors controlling the growth of at least the dominantspecies of the algal association is necessary. This information will alsohave appUed significance in the maintenance of adequate algal growth, aprerequisite for successful fish culture in these lagoons, regardless of whetheror not the fish grown feeds directly on the algae